PERBAIKAN GAMBARAN LESI ATEROSKLEROTIK DENGAN PEMBERIAN EKSTRAK BETA VULGARIS PADA TIKUS MODEL DIET ATHEROGENIK - Hardimarta, Fransisca Pramesshinta; Ikawati, Kartika; Yuniarti, Christina Ary (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
Atherosclerosis is characterized by the accumulation of fat in the arteries so it forms plaque that causes thickening of the intima and blockage of the arteries. Beet roots are rich of phytochemical compounds that have antioxidant activity. Design of research is a laboratory experimental study with a Post Test Only Randomized Control Group Design. The population of this study was male Wistar rats with age 2-3 months and body weight 125-200 grams. The study sample was randomly selected and consists of 7 groups and 5 rats for each group. The average number of foam cells in the baseline group is 17.6; negative control group is 65.8; positive control is 54.6; group I is 38.8; group II is 27.4; group III is 46.4; and group IV is 42.4. The average thickness of the aortic intima tunica in the baseline group is 136.8 µ; negative control group is 251.4 µ; positive control is 211.8 µ; group I is 202.8 µ; group II is 184 µ; group III is 242.8 µ; and group IV is 210.6 µ. Statistical test results showed that there were significant differences in supplementation of beet root extracts against aortic thickness and the number of foam cells in rats fed atherogenic diets.